Genetic diversity in two threatened species of guitarfish (Elasmobranchii: Rhinobatidae) from the Brazilian and Argentinian coasts: An alert for conservation - Cruz, Vanessa P. [UNESP]; Adachi, Aisni M.C. L. [UNESP]; Oliveira, Pablo H. [UNESP]; Ribeiro, Giovana S. [UNESP]; Paim, Fabilene G. [UNESP]; Souza, Bruno C. [UNESP]; Rodrigues, Alexandre S. F. [UNESP]; Vianna, Marcelo; Delpiani, Sergio M.; de Astarloa, Juan Martín Díaz; Rotundo, Matheus M.; Mendonça, Fernando F. [UNESP]; et al. (FapUNIFESP (SciELO), 2021)
The guitarfishes Pseudobatos horkelii and Pseudobatos percellens meet the criteria for threatened status as Critically Endangered (CR) and Endangered (EN), respectively. Both species occur in the Southern Atlantic Ocean. Considering the lack of data on the genetic structure of these species, the present study evaluated the genetic variability and population structure of the P. horkelii and P. percellens in the southern region of Brazil and the northern coast of Argentina, based on sequences of mitochondrial DNA, Control Region (D-loop). Samples of P. horkelii (n = 135) were analyzed in six localities situated in Northern Argentina, along the Brazilian states’ coast. The mean of nucleotide diversity was 0.0053, the ΦST was 0.4277 and demographic analysis of P. horkelii suggests the existence of stability of the populations, with D = 0.9929, FS = 2.0155, SSD = 0.0817, R = 0.2153. In P. percellens (n = 101) were analyzed from six Brazilian localities along the coast of Santa Catarina, Paraná, and São Paulo. The mean nucleotide diversity was 0.0014 and ΦST value of 0.2921, the demographic analysis indicates a high migration rate of P. percellens among the localities evaluated, with D = 0.5222, FS = 0.3528, SSD = 0.01785, R = 0.3890.
Keywords: D-loop; Endangered species; Populations; Pseudobatos horkelii; Pseudobatos percellens